Integrasi Pesantren dan Sekolah (Kajian atas Pemikiran Abdurrahman Wahid) - Herman Wicaksono (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2022)
Pesantren and schools should be integrated to the point where they both need to work together to improve the quality of education in Indonesia. Aside from the benefits and drawbacks of the pesantren education model, Abdurrahman Wahid, the "child" of pesantren, has demonstrated that pesantren can generate a nation's competent and competitive generation. As a result, the researcher was able to unearth Abdurrahman Wahid's views through library research involving books, kitab, periodicals, journals, and other connected materials. Abdurrahman Wahid has unique ideas regarding pesantren and school integration. Abdurrahman Wahid believes that this integration is critical in eliminating the knowledge divide and meeting the demands of today's career prospects. If the pesantren are still cut off from the new system that has joined the pesantren system, this will be impossible to do.